2021
DOI: 10.3389/fpsyg.2021.660234
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress and Smartphone Addiction in Medical College Students: The Mediating Role of Negative Emotions and the Moderating Role of Psychological Capital

Abstract: Background: Many studies have confirmed the existence of an extremely close relationship between smartphone addiction and perceived stress. However, the mediating and moderating mechanisms underlying the association between perceived stress and smartphone addiction in medical college students remain largely unexplored.Methods: A questionnaire was distributed among a total of 769 medical college students in Heilongjiang Province, China. Participants completed measures of perceived stress, smartphone addiction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 67 publications
(100 reference statements)
4
35
0
Order By: Relevance
“…This is consistent with the general strain theory which holds that all kinds of strain or stress experienced by individuals will lead to negative emotions and then lead to problem behavior ( Jun and Choi, 2015 ). Many studies have shown that stress is an important risk factor for individual addictive behavior ( Mai et al, 2012 ; Wang et al, 2021 ). The influence of perceived stress on smartphone addiction has begun to gain empirical support ( Chiu, 2014 ; Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the general strain theory which holds that all kinds of strain or stress experienced by individuals will lead to negative emotions and then lead to problem behavior ( Jun and Choi, 2015 ). Many studies have shown that stress is an important risk factor for individual addictive behavior ( Mai et al, 2012 ; Wang et al, 2021 ). The influence of perceived stress on smartphone addiction has begun to gain empirical support ( Chiu, 2014 ; Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This section presents the methodological information of the 35 studies included in the current review. As shown in Table 1 (See Appendix), majority of these studies have employed cross-sectional design (n=32) [12], [14], [17]- [22], [24], [27], [28], [30]- [50], which involve one-off data collection and study the relationship between stress and problematic smartphone use at a single point in time [51]. Only a few studies have employed longitudinal design (n=3) [13], [23], [29], which involve multiple waves of data collection and study the relationship between stress and problematic smartphone use at different points in time over a period of time [51].…”
Section: Methodological Information Of the Studies Reviewedmentioning
confidence: 99%
“…Only a few studies have employed longitudinal design (n=3) [13], [23], [29], which involve multiple waves of data collection and study the relationship between stress and problematic smartphone use at different points in time over a period of time [51]. Most of the studies reviewed are conducted in China (n=17) [12]- [23], [27]- [29], [35], [36], [41], [44], [45], [47]. Although they are relatively scant, some studies are also conducted in other countries such as Korea (n=3) [42], [43], [46], India (n=2) [33], [48], Malaysia (n=2) [14], [24], Turkey (n=2) [38], [39], United States (n=1) [13], Canada (n=1) [34], Netherlands (n=1) [31], Brazil (n=1) [49], Oman (n=1) [40], and Lebanon (n=1) [30].…”
Section: Methodological Information Of the Studies Reviewedmentioning
confidence: 99%
See 2 more Smart Citations